Reciprocal Packaging of the Main Structural Proteins of Type 1 Fimbriae and Flagella in the Outer Membrane Vesicles of “Wild Type” Escherichia coli Strains - Blackburn, Sarah A.; Shepherd, Mark; Robinson, Gary K. (Frontiers in Microbiology, 2021)
Fundamental aspects of outer membrane vesicle (OMV) biogenesis and the engineering of producer strains have been major research foci for many in recent years. The focus of this study was OMV-production in a variety of Escherichia coli strains including wild type (K12 and BW25113), mutants (from the Keio collection) and proprietary (BL21 and BL21(DE3)) strains. The present study investigated the proteome and prospective mechanism that underpinned the key finding that the dominant protein present in E. coli K-12 WT OMVs was FimA (a polymerizable protein which is the key structural monomer from which Type I fimbriae are made). However, mutations in genes involved in fimbriae biosynthesis (ΔfimA, B, C, F) resulted in the packaging of FliC (the major structural protein of flagella) into OMVs instead of FimA. Other mutations (ΔfimE, G, H, I and ΔlrhA - a transcriptional regulator of fimbriation and flagella biosynthesis) lead to the packaging of both FimA and Flagellin into the OMVs. In the majority of instances shown within this research, the production of OMVs is considered in K-12 WT strains where structural appendages including fimbriae or flagella are temporally co-expressed throughout the growth curve as shown previously in the literature. The hypothesis, proposed and supported within the present paper, is that the vesicular packaging of the major fimbrial protein monomer (FimA) is reciprocally regulated with the major flagella protein monomer (FliC) in E. coli K-12 OMVs but this is abrogated in a range of mutated, non-WT E. coli strains. We also demonstrate, that a protein of interest (GFP) can be targeted to OMVs in an E. coli K-12 strain by protein fusion with FimA and that this causes normal packaging to be disrupted. The findings and underlying implications for host interactions and use in biotechnology are discussed.